Impact of Transportation Barriers on Telehealth Use During the COVID-19 Pandemic - Jaewhan Kim PhD; Joshua Kelley MS; Seokjun Choi; Peter Weir MD (SAGE Publishing, 2024)
Telehealth use among individuals with and without transportation challenges remains understudied. This study aims to compare telehealth utilization and types of healthcare services between subjects with and without transportation challenges. Using data from the 2021 Medical Expenditure Panel Survey (MEPS), we identified telehealth use for office visits by adults (≥18 years old) in 2021, categorizing the type of healthcare services received, such as checkups and mental health counseling. Weighted logistic regression was employed to identify factors associated with telehealth usage. The total population analyzed was 204 621 985 (unweighted n = 17 674). The average (SD) age of the subjects was 49 (18) years old, and 53% were female. On average, individuals with transportation challenges had 1.40 telehealth visits, while those without such challenges had 0.87 visits ( P  = .03). Additionally, individuals with transportation challenges had more visits related to behavioral health compared to those without transportation challenges (22% vs 11%, P  < .01). Those facing transportation challenges were 40% more likely to use telehealth compared to those without transportation challenges (OR = 1.40, P  = .01). The findings suggest that telehealth could serve as a viable solution to overcome transportation barriers and improve access to care. However, it is crucial to assess access to care through telehealth to enhance the health outcomes for individuals facing transportation challenges.